Stress among medical students of a tertiary health care centre in tribal area of central India: a prospective observational study - Adikane, Hemant; Kaware, Alka; Thakre, Subhash (International Journal Of Community Medicine And Public Health, 2018)
Background: Medical education has been reported to be one of the most stressful academic curricula worldwide, negatively affecting the physical and mental health of medical students. A medical student can be stressed due to different reasons or stressors such as the academic, financial problem, health problem or loss of close family member or friend, etc. It is the person’s ability to face the everyday challenges which will determine whether he/she will be stressed or not. This stress manifests itself in a variety of forms, including burnout, depressive symptoms, poor Quality of Life, and fatigue. The greater the number of forms of stress experienced by an individual student, the higher the risk of recent suicidal ideation or serious thoughts of dropping out of medical school. Methods: Present observational study was conducted at Government Medical College, Gondia during July 2017 to April 2018. To collect the data, medical students’ stress questionnaire (MSSQ) was used. Results: Out of 100 study subjects approached, 98 subjects responded. At Ist session, Out of 6 domains, Academic related stressors was found to be highest (1.95±0.668) followed by Teaching and learning related stressors (1.39±0.81). Similarly in IInd session, similar results were exaggerated. Academic related stressors was found to be (2.00±0.61) followed by Teaching and learning related stressors (1.39±0.81). Conclusions: A large proportion of medical students have potential psychological problems. The stressors experienced by the students were mainly related to academics and psychosocial concerns.